Thermal analysis of concrete dams during construction phase - Santos, E. (2016)
This paper reports a case study of the thermal analysis of a concrete dam during its construction phase. The thermo-chemical problem is solved using a heat transfer model. In the absence of specific adiabatic calorimetric tests of the concrete, an exponential function was calibrated by the best fitting of estimated heat of hydration at the ages of 3, 7 and 28 days. The predicted temperatures obtained from the code are compared with the actual temperatures measured in situ by the monitoring system installed in the dam.